Penerapan Manajemen Nyeri pada Pasien Perioperative dengan Hidronefrosis di RSUD Labuang Baji Kota Makassar - Mohamad Fauzan Baso; Akbar Asfar; Rizky Iftitah Alam; Sajekti Tjahjaningrum (Wal'afiat Hospital Journal, 2025)
Hydronephrosis is a dilation of the renal pelvicalyceal system caused by urinary outflow obstruction, which may increase intrarenal pressure and trigger pain. This case report describes non-pharmacological pain management in a Perioperative hydronephrosis patient using deep breathing relaxation in the pre-operative phase and benson relaxation in the post-operative phase. The report followed the nursing process (assessment–diagnosis–intervention–implementation–evaluation). The primary Outcome was pain intensity using a 0–10 Numeric Rating Scale (NRS), complemented by physiological indicators (blood pressure, pulse, respiratory rate, temperature, oxygen saturation) and behavioral responses. In the pre-operative phase, pain decreased from NRS 4 to NRS 2 after deep breathing relaxation, along with improved vital signs. In the post-operative phase, pain decreased from baseline NRS 5 to NRS 3 after a 15-minute benson relaxation session and further to NRS 2 at the next follow-up (≈30 minutes), with a trend toward stabilized vital signs. Given the Perioperative setting, analgesics/anesthesia and the surgical procedure may confound pain Outcomes; therefore, findings are reported descriptively without attributing the changes solely to relaxation techniques. This case suggests that standardized relaxation techniques can be integrated into Perioperative nursing care to support comfort in hydronephrosis patients.